The development of air quality indices through image-retrieved AOT and PM10 measurements in Limassol Cyprus - Chrysoulakis, Nektarios; Themistocleous, Kyriacos; Retalis, Adrianos; Hadjimitsis, Diofantos G. (My University, 2012)
Research indicates that aerosol optical thickness (AOT) values and particulate matter (PM10) measurements can be used as indicators of atmospheric pollution. The problem of relating AOT with suspended particulate matter near the ground is still an open question. While satellite images can provide reliable and synoptic measurements from space, comparisons with monitoring surface level air pollution continues to be a challenge since satellite measurements are column integrated quantities. In this study, in-situ spectroradiometric measurements were taken during satellite overpass using field spectrometers to obtain the reflectance values of the calibration targets used. Sun photometer measurements were taken with the Microtops hand-held sun photometer to measure AOT. Meteorological data was collected from nearby meteorological stations and PM10 measurements were collected from local mobile air pollution stations. Following, the darkest pixel method of atmospheric correction was applied to a series of Landsat satellite images. The reflectance values of the atmospherically-corrected image were used in the radiative transfer equation to solve for AOT. Thematic maps were generated in order to develop air quality indices. The image-derived AOT values were examined for a positive correlation with PM10 measurements. It appears there exists a significant correlation between AOT and PM10 measurements. 2012 SPIE.
Keywords: Aerosols; Air pollution; Air quality; Maps; Meteorology; Optical properties; Optical radar; Particles (particulate matter); Photometers; Photometry; Reflection; Remote sensing; Satellite imagery; Space optics; Spectrometers; Spectroscopy; Aerosol optical thickness; Atmospheric corrections; LANDSAT satellite images; Particulate matter; Radiative transfer equations; Satellite measurements; Spectroradiometric measurements; Suspended particulate matters; Measurements; National Observatory of Athens; Foundation for Research and Technology-Hellas